Analisis Nilai Tambah Pengolahan Kopi Robusta di Ud. Cipta Lestari Desa Pujungan Kecamatan Pupuan Kabupaten Tabanan - Ni Gst. Ag. Gde Eka Martiningsih; Ida Ayu Made Dwi Susanti; Floriana Nonasal Edo (Jurnal MeA (Media Agribisnis), 2023)
This study aims to determine the amount of added value,processing system,as well as the eligibility obtained by robusta coffee processing businesses in UD Cipta Lestari in producing various coffee products. Research conducted in the processing business UD Cipta Lestari which is  one of the small – scale umkm, which produces robusta coffee products in the Village of Pujungan, Subdistrict of Pupuan Tabanan Regency.Processed products from Robusta coffee analyzed were wet coffee beans,dry coffee beans, roasted coffee and packaged coffee.The results of this research analysis that the income of the robusta Coffee Processing Unit in the UD Cipta Lestari Village of Pujungan, Subdistrict of Pupuan Tabanan Regency for the production proses robusta coffee as big Rp. 154.578.400/year. with acceptance 400 kg wet coffee beans as big Rp.43.200.000/year. For 100 kg dry coffee beans for Rp.54.000.000/year, For 80 kg roasting koffee of Rp.67.200.000/year. And for 80 kg packaged coffee as big as Rp. 86.400.000 with total receipts as big Rp.250.800.000/year.Meanwhile, the added value analysis which is obtained by the robusta Coffee Processing Unit in the UD Cipta Lestari Village of Pujungan, Subdistrict of Pupuan Tabanan Regency on the product robusta coffee is Rp. 71.778.400 with added value ratio 71,78 %. With greater added value  ≥ 50% hence robusta coffee processing in UD Cipta Lestari provide added value.